Kebijakan Kriminal Tindak Pidana Mayantara (Kajian Perlindungan Formulasi Hukum Pidana Indonesia Dengan Hukum Pidana Belanda) - Said Abdullah (Jurnal LEX SPECIALIS, 2010)
Criminalization of policy comparison mayantara crime in Indonesia carried out using the settings approach in the Penal Code by the settings in the concept of addition is made in particular settings in special legislation outside the Penal Code, while in the Netherlands is done by integrating into the Criminal Code Key Note : Comparative Criminal Law Formulation Indonesia by the Dutch Criminal Law